Antiviral effect of melatonin on Japanese encephalitis virus infection involves inhibition of neuronal apoptosis and neuroinflammation in SH-SY5Y cells - Kuntida Kitidee; Arisara Samutpong; Nattaporn Pakpian; Tanchanok Wisitponchai; Piyarat Govitrapong; Russel J. Reiter; Prapimpun Wongchitrat (My University, 2023)
Abstract Japanese encephalitis virus (JEV), a mosquito-borne flavivirus, causes high mortality rates in humans and it is the most clinically important and common cause of viral encephalitis in Asia. To date, there is no specific treatment for JEV infection. Melatonin, a neurotropic hormone, is reported to be effective in combating various bacterial and viral infections. However, the effects of melatonin on JEV infection have not yet been studied. The investigation tested the antiviral effects of melatonin against JEV infection and elucidated the possible molecular mechanisms of inhibition. Melatonin inhibited the viral production in JEV-infected SH-SY5Y cells in a time- and dose-dependent manner. Time-of-addition assays demonstrated a potent inhibitory effect of melatonin at the post-entry stage of viral replication. Molecular docking analysis revealed that melatonin negatively affected viral replication by interfering with physiological function and/or enzymatic activity of both JEV nonstructural 3 (NS3) and NS5 protein, suggesting a possible underlying mechanism of JEV replication inhibition. Moreover, treatment with melatonin reduced neuronal apoptosis and inhibited neuroinflammation induced by JEV infection. The present findings reveal a new property of melatonin as a potential molecule for the further development of anti-JEV agents and treatment of JEV infection.
Keywords: Neurotropic virus; Flavivirus; Viral encephalitis; Circadian rhythm and melatonin